Análisis de la cadena de valor del sector lácteo como instrumento de toma de decisiones para los productores de la cabecera cantonal de Saraguro, provincia de Loja periodo 2019-2020 - Ambuludi Lima, Segundo Fredy (2020)
This research aims to analyze the value chain of the dairy sector as a decision-making tool for producers in the Saraguro canton, through diagnosis, characterization, and proposal of an integration model that facilitates decision-making. For the analysis, it was convenient to use the guidelines set out in the research guide, Chains and Dialogue for Action series (CADIAC), which is useful for carrying out the diagnosis and characterization of the chain. The integration proposal is based on the model proposed by NGOs for Development Cooperation (CODESPA). The methods used are: exploratory in approaching the current situation, descriptive in identifying the behavior of the actors, synthetic in structuring the results, inductive in discussing the results, in addition to direct observation techniques in the area of study, bibliographic collection, interviews with managers, authorities, and surveys of livestock farmers. The identification of the population is based on data provided by the private company QUESOS SARAGURO and the community association SARALAC. The assessment presents the main actors in the sector, their strengths, constraints and bottlenecks. There are three activities, the first represented by cattle ranchers located in the rural and urban sector, the second transforming stage has several companies of which Quesos Saraguro and the SARALAC association are the most representative, finally, the commercialization activity is the least dynamic because it does not have marketing systems. Finally, it is concluded that the characterization facilitates the identification of bottlenecks, in the same way the diagnosis exposes the main strengths and weaknesses existing in the sector. To strengthen the chain, it is recommended that horizontal and vertical integration strategies be implemented.